(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Acrylamide was grafted onto cellulose backbone of old newspaper by CAN initiator in aqueous medium. Grafting parameter such as percentage grafting (GP%) and Grafting yield(GY%) was evaluated at different reaction conditions such as temperature, time, monomer and initiator concentration. Hence it was after 150 minutes (at Temperature of 50 0C, 2.5 g of CAN, 4 g of AAM) had highest GP% of 97% and GY% of 160% for CE-g-PAAM respectively. The products were characterized by FTIR and TGA analyses. Removal of heavy metals from wastewater was evaluated using the grafted copolymer. The results revealed promising potential of the grafted cellulose as adsorbent for remediation of waste water.